2019
DOI: 10.4236/jtts.2019.93022
|View full text |Cite
|
Sign up to set email alerts
|

Railway Transport Infrastructure Monitoring by UAVs and Satellites

Abstract: Improving the rail transport security requires development and implementation of neoteric monitoring and control facilities in conditions of increasing speed and intensity of the train movement and high level of terrorist threat. Use of Earth remote sensing (ERS), permitting to obtain information from large areas with a sufficiently high resolution, can provide significant assistance in solving the mentioned problems. This paper discusses the possibility of using various means of remote sensing such as satelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Ghassoun, et al (2021) used a multicopter to collect rail geometry data and calibrated the measurements by using the rail shoe as a reference (Ghassoun, et al, 2021). Ivashov et al (2019) found that combining images from satellites and drones in the visible and microwave frequency ranges has advantages in railroad security applications (Ivashov, Tataraidze, Razevig, & Smirnova, 2019). Craven (2017) demonstrated that drone-based photogrammetry can be effective at a height of 25 meters to avoid disrupting normal operations (Craven, 2017).…”
Section: Railway Tunnel Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghassoun, et al (2021) used a multicopter to collect rail geometry data and calibrated the measurements by using the rail shoe as a reference (Ghassoun, et al, 2021). Ivashov et al (2019) found that combining images from satellites and drones in the visible and microwave frequency ranges has advantages in railroad security applications (Ivashov, Tataraidze, Razevig, & Smirnova, 2019). Craven (2017) demonstrated that drone-based photogrammetry can be effective at a height of 25 meters to avoid disrupting normal operations (Craven, 2017).…”
Section: Railway Tunnel Monitoringmentioning
confidence: 99%
“…The large volume of data collected presents a variety of challenges such as the need for high-speed processing, rectification, referencing, and ground sampling (Singh, Swarup, Agarwal, & Singh, 2019). Some of the processing requires sophisticated deep learning methods and skills to analyze and interpret the results to inform decision making (Gantimurova, Parshin, & Erofeev, 2021) (Geng, et al, 2021) (Ivashov, Tataraidze, Razevig, & Smirnova, 2019). The appropriate lighting condition must be available for good quality image to automate measurements (Ghassoun, et al, 2021).…”
Section: Technical Challengesmentioning
confidence: 99%